PENERAPAN METODE PERAMALAN PADA PRODUKSI OFFICE FURNITURE UNTUK MENINGKATKAN STRATEGI DALAM SISTEM PENJUALAN (Studi Kasus: PT. KATWARA) - Muhamad Bangkit Kurniawan (LPPM Politeknik LP3I Medan, 2022)
ABSTRACTStock problems caused by incorrect production planning can be overcome by forecasting the production schedule so that the production planning schedule is accurate in the future. Future production planning will make it easier for the company in the process of determining the strategy and also the supply of raw materials needed. The object of this research focuses on office furniture products. The forecasting method used in this research consists of 2 (two) forecasting methods, namely Naive and Single Exponential Smoothing. The production schedule forecasting calculation is expected to be able to answer the problems that exist in the company. The determination of an accurate production schedule is determined by the results of the forecasting calculation with the smallest forecast error value as the final result of the study. Application of Single Exponential Smoothing Method on Office Furniture forecasting at PT. Katwara produces a data pattern that is close to or follows the pattern of production demand data, while the data pattern from the Naïve Method tends to be different from the production data. This happens because there is a difference in the calculation of the forecast value between the Naïve method and the Single Exponential Smoothing Method.The Exponential Smoothing method has a better accuracy rate than the Naïve method. The forecast error value of the Single Exponential Smoothing method is ME 2,316, MAD 59.575, MSE 5398.23 and MAPE 35.96%. While the Naïve method has a ME value of 4.067, MAD 68.2, MSE 7206.07 and MAPE 39.25%. The results of the forecasting of the Single Exponential Smoothing method can be a picture of the company in planning for the production of office furniture products in the future as well as being a reference in the appropriate raw material inventory strategy. Keywords: Forecast error, Naive, MAD, ME, MSE, MAPE, Office furniture, Single Exponential Smoothing